Low acuity and general practice‐type presentations to emergency departments: A rural perspective. (26th February 2015) - Allen, Penny; Cheek, Colleen; Foster, Simon; Ruigrok, Marielle; Wilson, Deborah; Shires, Lizzi
Abstract: Objective: To estimate the number of general practice (GP)‐type patients attending a rural ED and provide a comparative rural estimate to a metropolitan study. Methods: Analysis of presentations to the two EDs in Northwest Tasmania from 1 January 2009 to 31 December 2013 using the Diagnosis, Sprivulis, Australian College of Emergency Medicine (ACEM) and the Australian Institute of Health and Welfare (AIHW) methods to estimate the number of GP‐type presentations. Results: There were 255 365 ED presentations in Northwest Tasmania during the study period. There were 86 973 GP‐type presentations using the ACEM method, 142 006 using the AIHW method, 174 748 using the Diagnosis method and 28 922 low acuity patients identified using the Sprivulis method. Conclusions: The proportion of GP‐type presentations identified using the four methods ranged from 15% to 69%. The results suggest that triage status and self‐referral are not reliable indicators of low acuity in this rural area. In rural areas with a shortage of GPs, it is likely that many people appropriately self‐refer to ED because they cannot access a GP. The results indicate that the ACEM method might be most useful for identifying GP‐type patients in rural ED. However, this requires validation in other regions of Australia.